Empowering Leadership as the Primary Determinant of Teacher Performance: The Mediating Role of Innovative Work Behavior - Marwati Marwati; Syaiful Eddy; Reva Maria Valianti (Journal of Educational Sciences, 2026)
This study analyzes the role of empowering leadership as the primary determinant of teacher performance and explores the mediating mechanism of innovative work behavior in this relationship. Involving 95 teachers from three public senior high schools in Sungai Lilin District, Musi Banyuasin Regency, South Sumatra, this quantitative research examines the influence of empowering leadership and innovative work behavior on teacher performance. The findings confirm that empowering leadership is the main determinant of teacher performance and strongly supports the research hypothesis. Although innovative work behavior is related to performance, its influence weakens when considered alongside leadership, indicating it likely acts as an intermediary factor shaped by leadership. Together, both variables contribute to teacher performance, but they are not the only determinants, as other factors also play a role. These findings provide practical implications that developing school principals' empowering leadership capacity is a priority strategy for systematically improving teacher performance.